2019
DOI: 10.3390/microorganisms7120626
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Multidrug Resistance Profiles of Vancomycin-Resistant Enterococci Isolated from Two Wastewater Treatment Plants in the Same Municipality

Abstract: Wastewater treatment plants (WWTPs) are points of control for the environmental dissemination of antimicrobial resistant bacteria. Vancomycin-resistant enterococci (VRE) were used as indicators of antimicrobial resistance (AMR) in two WWTPs (biologically aerated filter (BAF) and conventional activated sludge (CAS)) in the same municipality. The removal and abundance of enterococci and VRE as well as the species and antimicrobial resistance profiles of VRE were assessed. Enterococci and VRE from the primary and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…In consequence, screening on VRESelect agar probably covers all vancomycin-resistant enterococci occurring in the wastewater of the sampled plant. This also applies to strains having low-level vancomycin resistance [ 44 ], which were detected in a previous environmental study [ 45 ] but could not be found among the tested isolates in this report.…”
Section: Resultssupporting
confidence: 50%
“…In consequence, screening on VRESelect agar probably covers all vancomycin-resistant enterococci occurring in the wastewater of the sampled plant. This also applies to strains having low-level vancomycin resistance [ 44 ], which were detected in a previous environmental study [ 45 ] but could not be found among the tested isolates in this report.…”
Section: Resultssupporting
confidence: 50%
“…However, studies reporting enterococci and their AR from the environment are scarce since enterococci are generally not considered important pathogens outside of hospitals and healthcare settings. A limited number of studies on environmental enterococci are mostly focused on water environments polluted by human inputs, such as wastewater, on species that are associated with human infections, such as E. faecalis and E. faecium, and on certain antimicrobial drugs, such as vancomycin [4][5][6][7]. Data concerning the presence of resistant enterococci in the aquatic environment is limited and still fewer data exists on the genetic content of waterborne antimicrobial resistant enterococci.…”
Section: Introductionmentioning
confidence: 99%
“…The strongest association among the resistance profiles was for vancomycin and ampicillin. Sanderson et al [60] and Martins da Costa et al [61] also observed a link between resistance to these two antibiotics, but further research is necessary to ascertain the mechanism of the relationship. We also observed a strong association of the resistance profiles for cefotaxime and amoxicillin clavulanate.…”
Section: Resistance To Individual Antibioticsmentioning
confidence: 99%